Age estimation in children based on open apices measurement in the Serbian population: Belgrade Age Formula (BAF) - Ksenija Zelic; Nemanja Marinkovic; Petar Milovanovic; Roberto Cameriere; Marija Djuric; Nenad Nedeljkovic (Taylor & Francis Group, 2020)
Background: Cameriere's method has been tested in many populations and is widely accepted for dental age estimation. Aim: To establish a new formula for age estimation by measurement of open apices of mandibular teeth based on Cameriere's European formula. Subjects and methods: Panoramic radiographs of 333 healthy Serbian children aged 5-14 years were analysed by two independent researchers. The new formula - Belgrade Age Formula (BAF) - was created and tested on the same Serbian sample. Furthermore, BAF was tested on the Serbian validation sample of 126 children and 2115 Italian children aged 5-14 years. Results: In the Serbian sample, the residuals of the BAF and European formula demonstrated that BAF is significantly better in age estimation than the European formula. No significant difference was found in females from the Serbian validation sample between dental and chronological age when BAF was applied. For males, the BAF and European formula had similar accuracy. In the Italian sample, the mean differences between estimated and real age for the European formula were −0.214 ± 0.934 and 0.109 ± 0.773 for females and males, respectively, while for BAF these differences were 0.182 ± 0.951 and −0.195 ± 0.923 for females and males, respectively. Conclusion: BAF was found to be accurate in the Serbian and Italian populations.